2011
DOI: 10.1002/da.20805
|View full text |Cite
|
Sign up to set email alerts
|

Feeling bad on Facebook: depression disclosures by college students on a social networking site

Abstract: Background Depression is common and frequently undiagnosed among college students. Social networking sites are popular among college students and can include displayed depression references. The purpose of this study was to evaluate college students' Facebook disclosures that met DSM criteria for a depression symptom or a major depressive episode (MDE). Methods We selected public Facebook profiles from sophomore and junior undergraduates and evaluated personally written text: “status updates.” We applied DSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
320
7
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 498 publications
(347 citation statements)
references
References 33 publications
(48 reference statements)
8
320
7
7
Order By: Relevance
“…Cohen's Kappa statistic is used to evaluate the extent to which there was overall agreement in the coding of the presence or absence of depression symptom references on a profile. In our previous work, Cohen's kappa was 0.79 for depression symptom references [5].…”
Section: Coder Trainingmentioning
confidence: 85%
See 1 more Smart Citation
“…Cohen's Kappa statistic is used to evaluate the extent to which there was overall agreement in the coding of the presence or absence of depression symptom references on a profile. In our previous work, Cohen's kappa was 0.79 for depression symptom references [5].…”
Section: Coder Trainingmentioning
confidence: 85%
“…These disclosures may include references to depression symptom in the form of "status updates," personally written text describing the profile owner's current experiences. Previous work found that approximately a quarter of publicly available Facebook profiles of undergraduates displayed depression symptom references, and a small proportion of profiles displayed depression symptoms in patterns consistent with the Diagnostic and Statistical Manual (DSM-IV) criteria for a major depressive episode (MDE) [4,5]. Additionally, display of depression symptoms was positively associated with reporting depression symptoms using a clinical screen [6].…”
Section: Introductionmentioning
confidence: 99%
“…But the study triggered an understandable flurry of outrage and concern for failing to inform or obtain consent from participants before attempting to manipulate their moods, as reflected in their Facebook updates (Calvo, Peters and D'Mello 2015). Moreno and Jelenchick (2011) manually evaluated a year's worth of status updates of 200 college students. Each update was coded against the DSM IV criteria for depression.…”
Section: Facebookmentioning
confidence: 99%
“…and the specific event they are attempting to predict. In [7], Moreno et al first demonstrated that social networking sites could be a potential avenue for identifying students suffering from depression. The prevalence rates found for depression disclosed on Facebook corresponded to previous works in which such information was self-reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, online social media networks have become one such informal resource. Research has shown that at-risk individuals are turning to contemporary technologies (forums, micro-blogs) to express their deepest struggles without having to face someone directly [6,7]. As a result, suicide risk factors and warning signs have been seen in a new arena.…”
Section: Introductionmentioning
confidence: 99%